Study on the assertiveness in stutterers - Mizumachi, T. (Japanese Journal of Behavior Therapy, 1987)
This study, consisting of two parts, was undertaken for the purpose of clarifying the assertiveness in stutterers. Part I The purpose of Part I was to examine the inter-group differences between stutterers and nonstutterers in assertiveness. A 36 item assertion scale was administered to 201 stutterers (mean age, 31.8) and 348 nonstutterers (mean age, 20.0). A factor analysis was carried out and four factors were extracted. These factors were interpreted as "expression of fair or foul" (factor I ), "loss of orientation in expression" (factor ), "expression of right or wrong" (factor III ), and "communication of intention" (facor N ). After factor scores of each subject on four factors were calculated respectively, the mean factor scores of each group were calculated, the result of which showed that stuttering group was higher in factor I and 1I than nonstuttering group, but lower in factor and N. Part II The purpose of Part II was to examine the intra-group differences among stutterers in asseriveness. According to their assertion scores, a high assertive group (N=48) and a low assertive group (N=50) were extracted from 201 stutterers in Part I and were compared with regard to their asseriveness. A factor analysis was carried out and three factors were extracted. These factors were labeled as "expression of fair or foul" (factor I ), "expression of right or wrong" (factor 11 ), and "loss of orientation in expression" (factor N ). The mean factor scores of each group on three factors were calculated, and its result indicated that a high assertive group was higher than a low assertive group in all three factors. Several tiems on how stutterers grasp their own stuttering were added to the 36 assertion items in stutterers. Thus the way that two groups grasp their respective stuttering was also compared with each other. In result, it was clarified that the low asserive group considered his stuttering symptoms more severe ones and was more distressed at his own stuttering problems than the high assertive group. Conclusions (1) The differences in assertiveness among stutterers are much greater than those observed between stutterers and nonstutterers. (2) We found a close relationship between assertiveness in stutterers and how stutterers grasp their own stuttering. This suggests that stuttering problems will be alleviated by having stutterers attain a more assertive way of life, and also that this alleviation of stuttering ploblems will make stutterers more assertive.